Antithrombotic Treatment after Transcatheter Heart Valves Implant - Sorrentino, Sabato; Giustino, Gennaro; Moalem, Kamilia; Indolfi, Ciro; Mehran, Roxana; Dangas, George D. (Seminars in Thrombosis and Hemostasis, 2018)
Transcatheter heart valve replacement technology was introduced as alternative to surgery for the growing high-risk profile population. Developed first, aortic valve replacement (TAVR) became a standard of care for patients with severe aortic stenosis at high operative risk, with a potential future use also for low-risk subjects. In the last decade, a multitude of transcatheter mitral valve replacement (TMVR) devices have been developed for the treatment of severe mitral regurgitation, with encouraging results coming from first-in-man and feasibility studies. As for biological surgical-type valves, transcatheter implanted valves still preserve the risk of thrombosis and embolic events and anticoagulation- or antiplatelet-based strategies are the most widely used options. Unfortunately, these last remain recommended on the basis of empirical or not widely validated evidence. Therefore, given the exponential rise of TAVR and TMVR procedures, it is important to identify the optimal antithrombotic strategies that best fit the risk of thromboembolic and bleeding events. Hereafter, this review evaluates the current guidelines, trials, and observational data discussing antithrombotic strategy after transcatheter aortic or mitral valve replacement.
Keywords: transcatheter heart valve replacement; antithrombotic therapy; valve thrombosis